2018
DOI: 10.5194/amt-11-3433-2018
|View full text |Cite
|
Sign up to set email alerts
|

A study of the approaches used to retrieve aerosol extinction, as applied to limb observations made by OSIRIS and SCIAMACHY

Abstract: Abstract. Limb scatter instruments in the UV-vis spectral range have provided long-term global records of stratospheric aerosol extinction important for climate records and modelling. While comparisons with occultation instruments show generally good agreement, the source and magnitude of the biases arising from retrieval assumptions, approximations in the radiative transfer modelling and inversion techniques have not been thoroughly characterized. This paper explores the biases between SCIAMACHY v1.4, OSIRIS … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 28 publications
6
49
0
Order By: Relevance
“…The two fitted parameters (α = 1.8 and β = 20.5) determined from the GD fit at 20 km produce an AE of 2.0 and a r eff of 0.18 µm. These values match the average values determined from SAGE II Version 7.0 data (Thomason et al, 2008;Damadeo et al, 2013) during the 2000-2005 period. Hereafter, this resultant ASD derived from the CARMA results will be labeled as V1.5 ASD, while the ASD assumed in LP V1 will be labeled as V1.0 ASD.…”
Section: Z Chen Et Al: Improvement Of Omps/lp Aerosol Retrievalsupporting
confidence: 83%
“…The two fitted parameters (α = 1.8 and β = 20.5) determined from the GD fit at 20 km produce an AE of 2.0 and a r eff of 0.18 µm. These values match the average values determined from SAGE II Version 7.0 data (Thomason et al, 2008;Damadeo et al, 2013) during the 2000-2005 period. Hereafter, this resultant ASD derived from the CARMA results will be labeled as V1.5 ASD, while the ASD assumed in LP V1 will be labeled as V1.0 ASD.…”
Section: Z Chen Et Al: Improvement Of Omps/lp Aerosol Retrievalsupporting
confidence: 83%
“…The aerosol extinction coefficient is retrieved by employing the general approach as used for SCIAMACHY v1.4 stratospheric aerosol extinction product (Rieger et al, 2017). As a consequence of a coarser spectral resolution, the radiance measured at 750 nm is affected by the O 2 absorption band.…”
Section: Aerosol Treatmentmentioning
confidence: 99%
“…The Ångström exponent (AE) is derived from Equation (1) using the 525 nm and 1020 nm extinction coefficients (Nyaku, 2016 Comparison of the extinction coefficients derived from OPC measurements and SAGE II occultation have shown differences that vary by more than 50% depending on altitude and for a volcanic period and less that 50% on the average for non-volcanic periods (Kovilakam and Deshler, 2015). Also Rieger et al (2018) have shown that the differences in the lognormal parameters can induce errors of 30% in the aerosol extinction retrievals for OSIRIS geometries and 50% for SCIAMACHY geometries when the correct AE is used. These analyses illustrate the importance of the assumed value of P a (Θ) for LS retrievals of K ext , 80 and the limitations of using AE alone to estimate the value of P a (Θ).…”
Section: Ae =mentioning
confidence: 99%